An aberrant sugar modification of BACE1 blocks its lysosomal targeting in Alzheimer's disease - Yasuhiko Kizuka; Shinobu Kitazume; Reiko Fujinawa; Takashi Saito; Nobuhisa Iwata; Takaomi C Saido; Miyako Nakano; Yoshiki Yamaguchi; Yasuhiro Hashimoto; Matthias Staufenbiel; Hiroyuki Hatsuta; Shigeo Murayama; et al. (EMBO Molecular Medicine)
Abstract The β‐site amyloid precursor protein cleaving enzyme‐1 (BACE1), an essential protease for the generation of amyloid‐β (Aβ) peptide, is a major drug target for Alzheimer's disease (AD). However, there is a concern that inhibiting BACE1 could also affect several physiological functions. Here, we show that BACE1 is modified with bisecting N‐acetylglucosamine (GlcNAc), a sugar modification highly expressed in brain, and demonstrate that AD patients have higher levels of bisecting GlcNAc on BACE1. Analysis of knockout mice lacking the biosynthetic enzyme for bisecting GlcNAc, GnT‐III (Mgat3), revealed that cleavage of Aβ‐precursor protein (APP) by BACE1 is reduced in these mice, resulting in a decrease in Aβ plaques and improved cognitive function. The lack of this modification directs BACE1 to late endosomes/lysosomes where it is less colocalized with APP, leading to accelerated lysosomal degradation. Notably, other BACE1 substrates, CHL1 and contactin‐2, are normally cleaved in GnT‐III‐deficient mice, suggesting that the effect of bisecting GlcNAc on BACE1 is selective to APP. Considering that GnT‐III‐deficient mice remain healthy, GnT‐III may be a novel and promising drug target for AD therapeutics.